2019
DOI: 10.3390/ijerph16071178
|View full text |Cite
|
Sign up to set email alerts
|

Does the Electronic Health Card for Asylum Seekers Lead to an Excessive Use of the Health System? Results of a Survey in Two Municipalities of the German Ruhr Area

Abstract: Background: The initial and intermediate-term access of refugees to healthcare in Germany is limited. A previous study showed that the obligation to request healthcare vouchers at the social security offices decreases the asylum seekers’ consultation rate of ambulant physicians. The introduction of the Electronic Health Insurance Card (EHIC) for asylum seekers is considered skeptically by some municipalities and federal states, among other reasons due to the fear of an overuse of health care services by asylum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…Our results showed that under restricted entitlements, the access model is associated with differences in specialist and emergency service use, but not with hospitalizations due to an ACSC. The differences attributable to the access model were smaller than differences found in comparisons of groups with restricted entitlements and regular SHI-like access [19,20,44]. We therefore assume that the entitlement restrictions for refugees exert higher influence on realized access than the local access model used.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our results showed that under restricted entitlements, the access model is associated with differences in specialist and emergency service use, but not with hospitalizations due to an ACSC. The differences attributable to the access model were smaller than differences found in comparisons of groups with restricted entitlements and regular SHI-like access [19,20,44]. We therefore assume that the entitlement restrictions for refugees exert higher influence on realized access than the local access model used.…”
Section: Discussionmentioning
confidence: 94%
“…Given the absence of differences for ACSC and the advantages of the eHC for outpatient use, the results should help to overcome wrong concerns of opponents of the eHC model who had anticipated that it might lead to an inadequate overuse of healthcare services among refugees [19,41]. Both models are implemented in other federal states of Germany in a similar way.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dies könnte dazu führen, dass Patient(inn)en zum einen die Inanspruchnahme ambulanter Versorgung verzögern und zum anderen vermehrt Notfallversorgungsangebote in Anspruch nehmen [21,22]. Eine standardisierte Befragung von Geflüchteten lieferte erste Hinweise, dass das eGK-Modell zu einer angemessenen Nutzung der gesundheitlichen Versorgung beitragen kann [23].…”
Section: Introductionunclassified
“…Unspecific symptoms that are often related to psychological distress, such as back pain and headaches, are highly prevalent and have been linked to somatization [ 8 ]. Asylum-seekers were shown to frequently seek healthcare from general practitioners, yet some studies point to underutilization of specialist health services [ 6 , 7 , 8 , 9 ]. High hospitalization rates, including high rates of ambulatory care-sensitive hospitalizations, have been reported [ 6 , 7 ].…”
Section: Introduction: the Health Of Lgbtiq Asylum-seekers—little mentioning
confidence: 99%